Need for speed - Rees, Elizabeth M.; Korman, Gordon; Disney Channel (Firm) (New York : Disney Press, 2001)
Elliott, disappointed by his failure to make the track team, learns some powerful lessons when a magic jersey lets him step into the body of track star Michael Johnson and race in a world-class event.
"Ages 8-12"--P. [4] of cover.
"Based on the series created by Gordon Korman.".
"Disney Channel.".
4.3.
4.3
3-6
Keywords: Magic -- Fiction; Track and field -- Fiction; Magic -- Fiction; Track athletics -- Fiction